Pro .NET 1.1 Remoting, Reflection, and Threading - Fahad Gilani, Syed; Pinnock, Jonathan; Hart, James; Mathew, Benny K.; Olsen, Geir; Pars, Robin; Ferracchiati, Fabio Claudio; Titus, Tobin; Redkar, Tejaswi; Sivakumar, Srinivasa; Gopikrishna, Sandra; Curran, David; et al. (Apress : Imprint: Apress, 2005)
Three powerful technologies-Remoting, Reflection, and Threading-are combined in a single book! And when these technologies come together, you are faced with a powerful range of tools that allow you to run code faster, more securely, and more flexibly. (And performance gains are critical in todays industry!) So you'll be able to code applications across the spectrum-from a single machine to an entire network. This book begins by discussing the most fundamental of the three techniques: .NET Remoting in Visual Basic .NET, which allows you to customize your application communication processes. The next portion of the book covers reflection, which allows you to examine code at run time, regardless of prior knowledge of its structure. Finally, the book explores threading, which helps break up your application into multiple, independent threads.